The TrkB agonist, 7,8-dihydroxyflavone, impairs fracture healing in mice - Johnstone, Maddison R. (J Musculoskelet Neuronal Interact, 2021)
OBJECTIVES: To study the effects of the selective TrkB agonist, 7,8-dihydroxyflavone (7,8-DHF), on fracture healing in mice and on an osteoprogenitor cell line, Kusa4b10, in vitro. METHODS: Mice received unilateral closed mid-shaft tibial fractures and treated for two weeks with vehicle or 5 mg/kg/day DHF and euthanised at 28 days post-fracture. Calluses were analysed by micro-computed tomography (µCT) and three-point bending biomechanical test. Kusa4b10 cells were cultured with 50nM of 7,8-DHF or vehicle for 3-, 7-, 14-days for RT-PCR, and 21 days for mineralization. RESULTS: µCT found 7,8-DHF calluses had decreased tissue volume (p=0.042), mean polar moment of inertia (p = 0.004), and mean cross-sectional area (p=0.042) compared to controls. At 28 days biomechanical analyses showed 7,8-DHF treatment decreased peak force (p=0.011) and stiffness per unit area (p=0.012). 7,8-DHF treatment did not change Kusa4b10 gene expression of Runx2 and alkaline phosphatase at all time points, nor mineralization. CONCLUSIONS: 7,8-DHF treatment had a negative impact on fracture healing at 28 days post-fracture via an unknown mechanism. 7,8-DHF may have had a central role in impairing fracture healing.